Proximity of first sexual intercourse to menarche and risk of high-grade cervical disease (2012)
Background We assessed if risk of developing cervical intraepithelial neoplasia grade 2/3 (CIN2/3) or adenocarcinoma in situ (AIS) is associated with a short interval between menarche and first sexual intercourse (FSI).Methods A total of 1009 Colombian and 1012 Finnish females, aged 16-23, who were enrolled in the phase 3 trials of a quadrivalent human papillomavirus (HPV) 6/11/16/18 vaccine had nonmissing data for age of menarche and FSI. The impact of menarche interval on the odds of developing CIN2-3/AIS was evaluated in placebo recipients who were DNA negative to HPV 6/11/16/18/31/33/35/39/45/51/52/56/58/59 and seronegative to HPV 6/11/16/18 at day 1, and had a normal Pap result at day 1 and month 7, thus approximating sexually naive adolescents (n = 504).Results The mean age of menarche and FSI was 12.4 and 16.0 years, respectively. Among the women approximating sexually naive adolescents, 18 developed CIN2-3/AIS. Compared with women who postponed FSI beyond 3 years of menarche, those with FSI within 3 years of menarche had a greater risk of cytologic abnormalities (odds ratio [OR], 1.65; 95% confidence interval [CI], 1.02-2.68; P =. 04) and CIN2-3/AIS (OR, 3.56; 95% CI, 1.02-12.47; P =. 05).Conclusions A short interval between menarche and FSI was a risk factor for cytologic abnormalities and high-grade cervical disease. These data emphasize the importance of primary prevention through education and vaccination.Clinical Trials Registration. NCT00092521 and NCT00092534. © 2012 The Author.